The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3758/mc.37.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Why are idioms recognized fast?

Abstract: It is an established fact that idiomatic expressions are fast to process. However, the explanation of the phenomenon is controversial. Using a semantic judgment paradigm, where people decide whether a string is meaningful or not, the present experiment tested the predictions deriving from the three main theories of idiom recognition-the lexical representation hypothesis, the idiom decomposition hypothesis, and the configuration hypothesis. Participants were faster at judging decomposable idioms, nondecomposabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 47 publications
12
105
2
Order By: Relevance
“…In fact, as Tabossi, Fanari and Wolf (2009) noted, idioms are familiar to most speakers, whereas matched literal sentences are fairly novel. This represents a potential confound in many idiom studies.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as Tabossi, Fanari and Wolf (2009) noted, idioms are familiar to most speakers, whereas matched literal sentences are fairly novel. This represents a potential confound in many idiom studies.…”
Section: The Present Studymentioning
confidence: 99%
“…On the one hand, the processing of the idiomatic constituents is often speeded up with respect to matched literal constituents in lexical decision tasks (Swinney & Cutler, 1979), in sentence verification tasks (Pesciarelli et al, 2014) or in reading comprehension tasks (Siyanova-Chanturia, Conklin & Schmitt, 2011;Vespignani, Canal, Molinaro, Fonda & Cacciari, 2010), as if idiomatic expressions were simply retrieved from semantic memory without any attempts to compose the meanings of the individual words. On the other hand, the processing time advantage of idioms, compared to literal sentences, has not been systematically replicated with all idiom types and methodologies (e.g., Tabossi Fanari & Wolf, 2009;Cacciari, Padovani & Corradini, 2007). Moreover, fMRI evidence attested a more widespread activation of the language network for idioms, extending to prefrontal areas (Boulenger, Hauk & Pulvermüller, 2009;Romero Lauro, Tettamanti, Cappa & Papagno, 2008;Zempleni, Haverkort, Renken & Sotwe, 2007; for a meta-analysis, see Bohrn, Altmann & Jacobs, 2012), that could be due to several factors including the competition engendered by the literal meaning and the figurative meaning of the expression (Romero Lauro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They found that idiomatic expressions in their figurative interpretation are read faster when they have high rather than low familiarity. Tabossi, Fanari, & Wolf (2009) explored the so-called idiom superiority effect: deciding that an idiom (e.g., break the ice) is a meaningful expression takes less time than deciding that a matched literal expression (e.g., break the glass) is meaningful. The phenomenon is well-known (Gibbs, 1980;McGlone, Glucksberg, & Cacciari, 1994;Ortony, Schallert, Reynolds, & Anton, 1978;Swinney, & Cutler, 1979), but its interpretation differs in the various models (Swinney & Cutler, 1979;Gibbs, Nayak, & Cutting, 1989;Cacciari & Tabossi, 1988).…”
Section: Familiaritymentioning
confidence: 99%
“…To date, most researchers agree that idioms are not processed as lexical items and form a very heterogeneous class, which varies in terms of syntactic flexibility and semantic analyzability (Cacciari & Glucksberg, 1991;Cacciari & Tabossi, 1988;Gibbs, 1992;Glucksberg, 1993;Nunberg, Sag, & Wasow, 1994). Various models have also been proposed to explain how these expressions are mentally represented and processed (Cutting & Bock, 1997;Sprenger et al, 2006;Tabossi, Fanari, & Wolf, 2009;Tabossi, Wolf, & Koterle, 2009). Also, interesting research is conducted on how children acquire the ability to use idiomatic expressions (Ackerman, 1982;Cacciari & Levorato, 1989;Gibbs, 1987Gibbs, , 1991Levorato & Cacciari, 1995;Levorato, Nesi, & Cacciari, 2004), how idiom knowledge and processing are disturbed in aphasic patients (Hillert, 2004;Papagno, Curti, Rizzo, Crippa, & Colombo, 2006;Papagno, Tabossi, Colombo, & Zampetti, 2004), and what structures in the brain are responsible for the processing of idioms and other types of figurative language (Sidtis Van Lacker, 2006).…”
mentioning
confidence: 99%
“…One potential problem with these studies is that some of the idiomatic sequences used in the experiments might not be familiar to L2 learners: If sequences such as the straw that broke the camel's back or up the creek without a paddle (Underwood et al, 2004) are unknown to learners, they are likely to present a processing disadvantage, as their meaning is not easily retrievable because of their lack of semantic transparency. Some studies (e.g., Tabossi, Fanari, & Wolf, 2009) have shown that knowing an idiomatic expression is what determines the speed at which it is processed, and recent studies usually include some tests of idiom familiarity (e.g., Carrol & Conklin, 2015).…”
Section: Speaker-external Approaches To Formulaicitymentioning
confidence: 99%